2011
DOI: 10.1016/j.ejpain.2010.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐centre European study of breakthrough cancer pain: Pain characteristics and patient perceptions of current and potential management strategies

Abstract: This study involved 320 cancer patients from four Northern European countries. Patients with breakthrough pain were questioned about the characteristics of their pain, the current management of their pain, and the acceptability/utility of alternative routes of administration. The median number of episodes was 3/day. Forty-four percent patients reported incident-type pain, 39% spontaneous-type pain, and 17% a combination of these pains. The median duration was 60 min, and the median time to peak intensity was 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
101
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(110 citation statements)
references
References 20 publications
4
101
0
5
Order By: Relevance
“…In addition, patients who had unstable background analgesia or more than four episodes of BTP/day were excluded. The criterion to define BTP was reported in previous studies [6,12,14,21]. From this sample, patients who were receiving opioids in doses of oral morphine equivalents equal or more than 60 mg daily were prescribed FBT in doses proportional to opioids used for background analgesia.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, patients who had unstable background analgesia or more than four episodes of BTP/day were excluded. The criterion to define BTP was reported in previous studies [6,12,14,21]. From this sample, patients who were receiving opioids in doses of oral morphine equivalents equal or more than 60 mg daily were prescribed FBT in doses proportional to opioids used for background analgesia.…”
Section: Methodsmentioning
confidence: 99%
“…The availability of supplemental doses of opioids (rescue medication) in addition to the continuous analgesic medication is the main treatment suggested to manage these pain flares [10]. For years, anecdotal experience has suggested that the starting effective dose of BTP medication must be a percentage of a patient's total daily opioid dose [6]. As pain relief is usually required urgently in the last decade, new routes of administration have been designed to provide fast pain relief.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although btcp can last up to 60 minutes, the typical duration of an episode is 15-30 minutes [3][4][5][6] . Another important distinguishing characteristic of btcp is its rapid onset, with escalation to maximum intensity in as little as 1 minute [3][4][5][6][7] . The frequency of the pain episodes can vary from a single time to several times daily or weekly 7,8 .…”
Section: In 2009mentioning
confidence: 99%
“…BTcP differs from BCP due to its high intensity (numerical rating score [NRS], 7), the short time interval between onset and peak intensity (median interval, 3 minutes to peak pain), short duration (median, 30 to 60 minutes), potential recurrence over 24 hours (3-4 daily episodes), and non-responsiveness to treatments for BCP [3,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%